FAKTOR-FAKTOR INTERNAL YANG MEMPENGARUHI WAKTUPENYELESAIAN PERKULIAHAN MAHASISWA PROGRAM STUDIPENDIDIKANTEKNIK BANGUNAN JURUSAN TEKNIK SIPILFT-UNP - 703-711 , Febry Sandy (Universitas Negeri Padang, 2015)
Abstract This researchaims to determine of the most dominant internal factors to completion the study in college.The type of this researchis quantitative descriptive. The student in this research is student has been finished the study more than 7 semesterBP2008, 2009, 2010 and 2011amounted to174 student. Samplingusing is anomogramHarryKingwith aconfidence level of 95% that obtained a sampleof 125students. The techniques collection data using aquestionnairewithLikert scale. The techniques analyzed data using is a descriptive analysis. Results fromthis research thatmotivation is themost dominant factoraffecting tocompletion the studycollegestudents ofEducation Building TechnicalMajoring in Civil EngineeringFaculty of Engineering Padang State University with the degree ofachievementof75.14% with amajorassessment categories. Keyword: Faktor Internal, Waktu Penyelesaian, Kuliah